Impact of statin therapy on plasma adiponectin concentrations: A systematic review and meta-analysis of 43 randomized controlled trial arms - Chruściel, Piotr; Sahebkar, Amirhossein; Rembek-Wieliczko, Magdalena; Serban, Maria-Corina; Ursoniu, Sorin; Mikhailidis, Dimitri P.; Jones, Steven R.; Mosteoru, Svetlana; Blaha, Michael J.; Martin, Seth S.; Rysz, Jacek; Toth, Peter P.; et al. (Atherosclerosis, 2016)
The effect of statin therapy on plasma adiponectin levels has not been conclusively studied. Therefore, we aimed to evaluate this effect through a systematic review and meta-analysis of available randomized controlled trials (RCTs). Quantitative data synthesis was performed using a random-effects model with weighted mean difference (WMD) and 95% confidence interval (CI) as summary statistics. In 30 studies (43 study arms) with 2953 participants, a significant increase in plasma adiponectin levels was observed after statin therapy (WMD: 0.57 μg/mL, 95% CI: 0.18, 0.95, p = 0.004). In subgroup analysis, atorvastatin, simvastatin, rosuvastatin, pravastatin and pitavastatin were found to change plasma adiponectin concentrations by 0.70 μg/mL (95% CI: −0.26, 1.65), 0.50 μg/mL (95% CI: −0.44, 1.45), −0.70 μg/mL (95% CI: −1.08, −0.33), 0.62 μg/mL (95% CI: −0.12, 1.35), and 0.51 μg/mL (95% CI: 0.30, 0.72), respectively. With respect to duration of treatment, there was a significant increase in the subset of trials lasting ≥12 weeks (WMD: 0.88 μg/mL, 95% CI: 0.19, 1.57, p = 0.012) but not in the subset of <12 weeks of duration (WMD: 0.18 μg/mL, 95% CI: −0.23, 0.58, p = 0.390). Random-effects meta-regression suggested a significant association between statin-induced elevation of plasma adiponectin and changes in plasma low density lipoprotein cholesterol levels (slope: 0.04; 95% CI: 0.01, 0.06; p = 0.002). The meta-analysis showed a significant increase in plasma adiponectin levels following statin therapy. Although statins are known to increase the risk for new onset diabetes mellitus, our data might suggest that the mechanism for this is unlikely to be due to a reduction in adiponectin expression. [Display omitted] •The effect of statin therapy on plasma adiponectin levels has not been conclusively studied.•The analysis shows a significant increase in plasma adiponectin levels after statin therapy (WMD: +0.57 μg/mL).•The meta-analysis confirmed that statins may have an important impact on the adiponectin levels.•The pleiotropic adiponectin-elevating effect of statins might explain the benefits of statins in reducing the CV risk.